Dynamic Structures of DNA Heptamers with Different Central Trinucleotide Sequences Studied by Electrochemical and Spectral Methods. Issue 10 (15th September 2014) - Pilarova, Iveta; Kejnovska, Iva; Vorlickova, Michaela; Trnkova, Libuse
Abstract A short, single‐stranded DNA fragment d(GCGAAGC) and its analogs d(GCNNNGC) carrying different trinucleotide sequences in the center of the molecule (AAA, CCC, GGG or TTT) were investigated by spectral (CD and UV spectra) and electrochemical methods (voltammetry, polyacrylamide gel electrophoresis). Our results show that (i) the central triplet GAA or AAA dramatically stabilizes DNA hairpins, (ii) a stem‐loop configuration is not supported by CCC or TTT sequences, instead, these heptamers adopt bimolecular duplex forms. Finally (iii), in the case of GGG sequence a very stable supramolecular G‐quadruplex is formed.